XPS analysis of ZnO: ga films deposited by magnetron sputtering: substrate bias effect - Correia, Filipe Costa (2018)
This work focuses on X-ray photoelectron spectroscopy (XPS) and combined Raman and photoluminescence experiments performed on ∼500 nm thick ZnO:Ga films deposited by magnetron sputtering. The substrate bias voltage applied during the deposition was varied between 0 V (grounded) and −120 V in order to study the effect of Ga-doping on the ZnO wurtzite structure of the films and its electrical properties, when using a fixed doped composition of Ga2O3 (4.5 wt.%) in the ZnO sputtering target. XPS analysis revealed that ZnO dominates in all samples, while the Ga amount is the highest (∼2.9 at.%) for a substrate bias polarization of −60 V, diminishing substantially for either decreasing or increasing substrate polarizations. This increase in Ga con centration is responsible for the enhancement of electronic transport properties, resulting in a minimum elec trical resistivity of ∼300 µΩ·cm. Moreover, the atomic layers closer to the surface are deficient in zinc for higher bias, due to the etching effect of Ar+ ions and subsequent Zn re-evaporation. From the Raman experiments, it was observed that the dynamics of the A1 and E1 phonons correlates with the decrease of the electrical resistivity. Photoluminescence studies revealed two broad bands, being one near the ZnO near-band-edge (3.4 eV) and another at higher energies (∼3.6 eV). The band centered at higher energies is more prominent for the case of the more electrically-conductive films, and is ascribed to electron transitions from the conduction band to single ionized oxygen vacancies. The lifetime of the polar-nature longitudinal optical phonons is in the range of 0.1–0.2 ps, which is quite small due to the Fröhlich interactions with gallium dopant atoms and other defects